GAMBARAN KADAR GLUKOSA DARAH SEWAKTU PADA PETUGAS AVIATION SECURITY BANDARA JUWATA TARAKAN DENGAN INDEKS MASSA TUBUH 17-27 kg/m2 - Setiyawan, Agung (Jurnal Kesehatan Masyarakat (Undip), 2016)
Blood sugar levels are affected by several factors such as knowledge, age, gender, heredity, diet, smoking, and physical activity. Lifestyle changes such as shifting diet with less fiber and foods high in sugar. This becomes a risk factor for overweight and if it last continsuously will increase incidence of diabetes mellitus. This study aims to describe blood sugar levels when the officer Aviation Security service Tarakan Juwata with a Body Mass Index (BMI) 17-27 kg/m2. This research is descriptive. Respondents consisted of male and female 41 persons for 5 people. Data obtained with a Body Mass Index measurements and laboratory test are random blood sugar levels. The results showed that out of 46 respondents consisted of 41 men (89,1%) and 5 women (10,9%), as many 27 people (58,7%) had normal blood sugar levels. Based on the results of this study concluded that the Aviation Security service officers Juwata Tarakan with BMI 17-27 kg/m2 most have blood glucose levels as normal. Suggestions for the respondents to stop smoking, exercise regularly, avoid obesity, and health checks regularly.